Effects of plasma transfusions on antithrombin levels after paediatric liver transplantation. Issue 6 (15th May 2018) - Arni, D.; Wildhaber, B. E.; McLin, V.; Rimensberger, P. C.; Ansari, M.; Fontana, P.; Karam, O.
Abstract : Background and Objectives: Thrombotic complications affect 3–10% of patients after liver transplantation (LT), leading to potentially life‐threatening complications. In the days following LT, antithrombin (AT) is decreased longer than pro‐coagulant factors, thus favouring a pro‐thrombotic profile. Plasma transfusions are given empirically in some centres to correct AT levels following LT. We assessed the effect of plasma transfusion on AT levels after paediatric LT. Materials and Methods: Prospective single‐centre observational study in 20 consecutive paediatric LT recipients over a 24‐month period. Plasma was administered twice daily (10 ml/kg/dose) according to an existing protocol. AT levels were measured once daily, immediately prior to and one hour after the morning plasma transfusion. Sample size was calculated based on a non‐inferiority hypothesis. Results: The median age and weight were 11.6 years (IQR 2.8; 14.7) and 40 kg (IQR 12.75; 44.8), respectively. We collected 85‐paired blood samples. The median AT level prior to plasma transfusion was 58%. The median difference in AT levels before and after plasma transfusion was 4.2% ( P = 0.001). Changes in AT levels after plasma transfusion were not correlated with baseline AT levels ( R = 0.19) or patient weight ( R = 0.18). Conclusion: Plasma transfusions only marginally increase AT levels in children after LT. Therefore, prophylactic plasma transfusions probably do not seem to confer an advantage in the routine management of paediatric LT patients. Randomized controlled trials are needed to identify the optimal anticoagulation strategy in this specific population.